ANALYSIS OF MANAGEMENT KNOWLEDGE FACTORS ON EMPLOYEE PERFORMANCE PROCESS IN INCREASING INCOME (Case Study of Tambakmekar Sejahtera Business Unit) - Ria Nuroktoviani; Rahmat Hidayat; Silpia Fitri Patonah (STIESA Press, 2023)
This study aims to see how the influence of management in improving the economy in Village OwnedEnterprises (BUMDes) whose goal is to prosper the Tambakmekar village community. The level of success in increasing income and performance will be reviewed in more detail in the Tambakmekar Bumdes. The research method used is a qualitative research method, accompanied by data taken frominterviews with 1 village-owned enterprise management manager and 4 employees who are responsiblefor the Blooming Pond business unit. The results of research that has been reviewed show that the results of BUMDes management are nailed in village business units that can be enjoyed by village communities. BUMDes is able to be an effective strategy in seeing the potential possessed by the village whose aim is to increase village income. The process of performance effectiveness aims to develop human resources in managing the business that has been developed. The strategy used is to manage BUMes with a financial management system, marketing,distribution and human resources.